A Novel Multilevel Converter with Stable Voltage to The Renewable Energy Systems (International Journal of Innovative Research in Engineering & Management, 2021)
In this proposed paper, a novel nine-level inverter (NLI) topology  is proposed, which uses fewer components to provide nine  voltage levels in the output. Ten semiconductor switches, four  capacitors, and one dc voltage source are included in this NLI.  Through various logical arrangements of the dc source and  capacitors and the use of power semiconductor switches, the nine  voltage levels are generated. In this case, only two switches can  conduct simultaneously in any mode. As a result, the system's  efficiency is increased and conduction losses are decreased. The  low total standing voltage (TSV) of the power semiconductor  switches is another crucial aspect of this design. Gate signals are  produced using a suggested modulation approach to lessen the  power switches' switching loss. Several Simulink simulations are  run in order to validate the NLI. The suggested inverter has a  much lower requirement for components and dc sources as  compared to conventional topologies. In order to increase the  efficiency of the power generating process in renewable energy  systems, the proposed NLI structure can be implemented.
Keywords: Multilevel; Renewable; Energy Systems